Prediction of Groundwater Temperature Variation in Riverine Well for the Safe Operation of Groundwater Heat Pump (GWHP) System - Ko, Il Jin; Choe, Tok Gi (Clean Energy Technologies, 2025)
Riverbank filtration is used for producing a large amount of groundwater for a long time. The surface water infiltration is accompanied with riverbank filtration and may significantly affect the quality and temperature of pumping water if the pumping well is located nearby the river. A coupled groundwater flow and heat transport model was developed to estimate the influence of surface water on the temperature in pumping well for groundwater heat pump system at the riverbank. The model included the aquifers under river and considered the variation of surface water temperature with season and depth to simulate accurately pumping water temperature. To depict in detail the aquifers and riverbed sediment in contact with the river, the 3D geological model was developed by Geomodeller, and the numerical model was completed by FEFLOW. For model calibration, the simulation results were compared to the measured groundwater level and temperature data in pumping well during 2 years. The result showed high accuracy with the coefficient of determination (R2) of 0.971, root mean square error (RMSE) of 0.211 ℃. Using calibrated model, the groundwater temperature changes in pumping well were predicted for 15 years. The proposed modeling method can be used to estimate the groundwater flow, quality, and temperature change by the surface water infiltration in riverine aquifer.